High temperature flexural strength and oxidation behavior of hot-pressed B4C–ZrB2 ceramics with various ZrB2 contents at 1000–1600 °C in air. (June 2016) - He, Rujie; Zhou, Zhili; Qu, Zhaoliang; Cheng, Xiangmeng
Abstract: High temperature flexural and oxidation behavior of hot-pressed B4 C–ZrB2 ceramics with various ZrB2 addition amounts was measured and analyzed in the temperature range of 1000 to 1600 °C in ambient air atmosphere. The high temperature flexural strength is a strong function of temperature. With the temperature increasing, the high temperature flexural strength decreases. The oxidation behavior was investigated in detail, and the oxidation mechanism was summarized. The purpose of this study is to give fundamental understanding of the high temperature behavior of B4 C based ceramics. Highlights: High temperature flexural of B4 C–ZrB2 ceramics were measured in air. Oxidation behaviors of B4 C–ZrB2 ceramics were investigated. Effects of ZrB2 addition were studied.